Telenursing interventions in lung cancer patients on chemotherapy: a systematic review - A. De Leo; G. Liquori; E. Di Simone; A. Spano; N. Panattoni; L. Iacorossi; N. Giannetta; S. Dionisi; M. Di Muzio; F. Petrone (World Cancer Research Journal, 2024)
Objective: Patients with lung cancer patients report a worse quality of life than other cancer patients. Telenursing interventions should represent effective solutions in their clinical pathways. The study aims to provide an overview of telenursing interventions in lung cancer patients on chemotherapy.